Reliability of lumbar movement dysfunction tests for chronic low back pain patients. (August 2016) - Bauer, Christoph Michael; Heimgartner, Martin; Rast, Fabian Marcel; Ernst, Markus Josef; Oetiker, Sarah; Kool, Jan
Abstract: Assessment of lumbar movement dysfunction commonly comprises trunk range of motion (ROM), movement or control impairment (MCI), and reposition error (RE). Those assessments are typically based on visual observation. Consequently it is not possible to reliably quantify back movements for intersubject comparisons, or for monitoring changes before and after an intervention. Inertial measurement unit (IMU)-systems could be used to quantify these movement dysfunctions in clinical settings. The aim of this study was to evaluate the reliability of movement dysfunction tests when measured with a novel IMU-system. The reliability of eleven movement dysfunction tests (four ROM, six MCI and one RE tests) were analysed using generalizability-theory and minimal detectable change, measuring 21 chronic low back pain patients in seven trials on two days. Reliability varied across tests and variables. Four ROM and selected MCI tests and variables were identified as reliable. On average, ROM test were more reliable, compared to MCI and RE tests. An attempt should be made to improve the reliability of MCI and RE measures, for example through better standardizations. Subsequently these measures should be studied further for intersubject comparisons and monitoring changes after an intervention. Highlights: Range of motion can and movement control can partly be reliably measured in CLBP patients. Reposition error cannot be measured reliably in CLBP patients. Recommendations are given for reliable measurement protocols.